2014
DOI: 10.1155/2014/975303
|View full text |Cite
|
Sign up to set email alerts
|

Clot Lysis and Antimitotic Study of Ficus glomerata Roxb Fruit Extracts

Abstract: The present study was carried out to investigate the thrombolytic and antimitotic potentiality of various extracts of fruits of Ficus glomerata, a traditional medicinal plant, using an in vitro assay method. Three crude extracts such as petroleum ether (FGPE), chloroform (FGCE), and methanol (FGME) were used for the study, with a standard (streptokinase) and negative control (sterile distilled water) to validate the method. The thrombolytic nature of the plant was found significant with methanol extract and ch… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Statistical analysis revealed that the rhizome extracts have a significant percentage of clot lysis when compared with positive and negative control. As the first generation drugs (SK and UK), found to cause side effects [17], plant-based thrombolytic drugs will improve the treatment of thrombosis. Therefore, in-vivo study of C. amada and C. caesia is further needed, to be recognized as a thrombolytic agent.…”
Section: Resultsmentioning
confidence: 99%
“…Statistical analysis revealed that the rhizome extracts have a significant percentage of clot lysis when compared with positive and negative control. As the first generation drugs (SK and UK), found to cause side effects [17], plant-based thrombolytic drugs will improve the treatment of thrombosis. Therefore, in-vivo study of C. amada and C. caesia is further needed, to be recognized as a thrombolytic agent.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the presence of phytochemicals, C. decidua fruits were also found to possess thrombolytic efficacy as shown in Table 2. Several plant species have been screened for in vitro thrombolytic potential [13,21] and some of the plants have shown similar in vitro percent thrombolytic potential for example, 32.58% clot lysis activity by leaves of Leea indica [22], 31.61% by leaves of Senna sophera and 31.51% fruits of Solanum torvum [23], 23.11% by chloroform extract of fruits of Ficus glomerata [24], 30.17% and 22.53% clot lysis by bark and seeds of Tamarindus indica respectively [25], 32.94% by seeds of Sesamum indicum [26], etc.…”
Section: Discussionmentioning
confidence: 99%
“…Statistical analysis revealed that the rhizome extracts have a significant percentage of clot lysis when compared with positive and negative control. As the first generation drugs (SK and UK), found to cause side effects 12,13 , plant-based thrombolytic drugs will improve the treatment of thrombosis. The methanolic leaf extract of Euphorbia hirta have maximum activity for lysing the clot.…”
Section: Discussionmentioning
confidence: 99%